Preliminary study on compressible gas-liquid two-phase flow computation for ultra-high-pressure fuel injection process - Takahiro SUMI; Takuji KUROTAKI; Katsuyuki OHSAWA; Tetsuya ODA (Nihon Kikai Gakkai ronbunshu, 2019)
To obtain qualitative knowledges about an ultra-high-pressure fuel injection process in a future automobile diesel injector, a compressible gas-liquid two-phase flow solver is newly developed and an unsteady numerical analysis on a simple injection system with a two-dimensional micro-hole is performed. The six-equation diffuse interface model with heat and mass transfer is adopted and extended from the original two-phase two-component system to the new two-phase multi-component system. High-order numerical discretization methods in time and space are employed to resolve fine flow structures in the transient injection process. In the numerical results, injection pressure in the high-pressure chamber and back pressure in the low-pressure chamber are systematically changed, and the effects on the injection process are discussed in detail. Under conditions close to real operation, promotion of primary atomization due to jet instability, formation of a detached shock wave at the tip of the fuel jet and generation of cavitation bubbles inside the hole are clearly observed. Moreover, compressible effects in both gas and liquid phases are confirmed to be crucial in the numerical analysis of the ultra-high-pressure fuel injection process, which integrally handles the whole system from the high-pressure section to the low-pressure section.